Core-rim structured carbide MXene/SiO2 nanoplates as an ultrathin microwave absorber. (November 2020) - Guo, Rui; Fan, Yuchi; Wang, Lianjun; Jiang, Wan
Abstract: Despite the high microwave attenuation ability of the titanium carbide MXene, exploiting the two-dimensional (2D) material as an efficient microwave absorber is a challenging task due to the strongly reflective feature caused by high electrical conductivity. Here, the plate-like MXene/SiO2 composites with a unique core-rim microstructure (MXene@SiO2 ) are rationally constructed by a simple Stöber method. The abundant functional groups on the edge of MXene leads to the formation of thick rim on MXene@SiO2 nanoplates, which remarkably increases the interfacial polarization loss. Meanwhile, the SiO2 coating with tunable thickness can balance the impedance at surface, which largely prevents the reflection of incident microwaves. As a result, very low specific reflection loss of −34.33 dB mm −1 in X band and −55.68 dB mm −1 in Ku band are realized in the composite with optimized coating thickness. Moreover, the reflection loss lower than −20 dB (MA efficiency more than 99%) can always be achieved with certain matching thickness lower than 2 mm in the whole X and Ku band. These findings imply that the 2D core-rim MXene@SiO2 nanoplates can be applied as ultrathin microwave absorber in various portable devices. Graphical abstract: Image 1 Highlights: Unique 2D core-rim structured carbide MXene/SiO2 nanoplates are fabricated. Core-rim structure remarkably increases the interfacial polarization loss. The SiO2 coating can well balance the impedance match and attenuation constants. High microwave absorbing efficiency with ultra-low matching thickness is achieved.